Um aplicativo para gerar recomendações e alertas sobre a qualidade do ar em um smart campus - Rodrigues, Pablo Leon (2020)
The population increase in urban areas demands an increase of basic services in cities such as energy consumption and increased traffic. As a consequence, energy consumption through non-renewable sources such as fossil fuels also increases, as does the pollution generated by industrial and burning processes, contributing to air pollution. The World Health Organization estimates that 4.2 million deaths per year are due to exposure to polluting gases in the environment and that 91 % of the world population lives in areas where air pollution exceeds acceptable limits. The monitoring of air quality in Brazil is done in part by state agencies, and there is currently no comprehensive monitoring coverage. Information is obtained during the census that occurs every ten years conducted by the Brazilian Institute of Geography and Statistics, for the next census to be conducted in 2020 the estimated cost is approximately three billion reais. Given these facts, the need arises to constantly monitor the environment in which we live. Through the use of a low-cost network to collect data obtained from monitoring air quality within a university campus, the work presented proposes the development of a mobile application aimed at the academic community presenting information, recommendations and alerts on the quality of the on-campus air to minimize exposure and permanence in environments where air pollution becomes harmful to health.